Light Steel Framing and Structural Concrete Walls: Sustainable Perspectives for Affordable Housing - Gurgulino, João; Saraiva, Raphael; Tatiana, Maruska (European Journal of Sustainable Development, 2017)
The emerging countries’ society has demanded an increase on investments for affordable housing to long forgotten communities with low income – along, customarily, with the mind-set of sustainable development. In the past years, Brazil, for instance, has had an expansion on government programs that subsidize low-cost housing and, thus, studies on this area become more needed. In this paper, the sustainable aspects of two construction methods (Light Steel Framing and Structural Concrete Walls) are reviewed. The theories involving both methods and their practical approach are compared to their economical, ecological and social standards – aiming to identify the more sustainable one. Local aspects such as the supplying of materials, the work force expertise and the possible social obsolesce projections are fairly granted for both techniques. Hence, it was possible to track one construction site of the extension of approximately 1600 houses on Structure Concrete Walls and another one of a single house on Light Steel Frame, which is then extrapolated to an extent of several houses for comparison. Furthermore, based on the sustainable standards (economical, ecological and social), the Light Steel Frame mechanism has demonstrated to be superior in all standards when applied to the geographic conditions. Keywords: Light Steel Frame, Structural Concrete Walls, Sustainability